2008
DOI: 10.1093/toxsci/kfn044
|View full text |Cite
|
Sign up to set email alerts
|

Khat (Catha edulis) Induces Reactive Oxygen Species and Apoptosis in Normal Human Oral Keratinocytes and Fibroblasts

Abstract: Khat chewing is widely practiced in Eastern Africa and the Middle East. Khat is genotoxic to cells within the oral mucosa, and several studies have suggested an association between khat use and oral lesions like hyperkeratosis and oral cancer. This study investigated the mechanism of khat-induced cytotoxicity using primary normal human oral keratinocytes (NOK) and fibroblasts (NOF). Khat induced rounding up of cells, plasma membrane blebbing, and condensation of nuclear chromatin within 3-6 h of exposure. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 35 publications
5
42
0
Order By: Relevance
“…Our result confirms the previously reported studies, which exhibits the depletion of GSH in long-term Khat chewers or experimental animals treated with Khat extract [17,30]. This enhancing the idea that GSH is strong cellular antioxidants, which effectively scavenges reactive oxygen species (e.g., hydroxyl radical, lipid peroxyl radical and H 2 O 2 ) and other free radicals directly and indirectly through enzymatic reactions [38].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our result confirms the previously reported studies, which exhibits the depletion of GSH in long-term Khat chewers or experimental animals treated with Khat extract [17,30]. This enhancing the idea that GSH is strong cellular antioxidants, which effectively scavenges reactive oxygen species (e.g., hydroxyl radical, lipid peroxyl radical and H 2 O 2 ) and other free radicals directly and indirectly through enzymatic reactions [38].…”
Section: Discussionsupporting
confidence: 93%
“…This result confirms the similar elevation of MDA induced by Khat [16,17,30,41]. Elevation level of MDA reflects the lipid peroxidation that occurred by radicals, from a polyunsaturated lipid abundant in the cell membranes, and this amplifies the damage of cell membrane.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Second, khat-induced oxidative stress and apoptosis has also been observed by other researchers. 5 Both observations 2,5 are consistent with short-and long-term genotoxic and cardiac effects on khat chewers. We strongly believe that future studies should also focus on finding a link between pesticide exposure and acute coronary syndrome complications.…”
Section: To the Editorsupporting
confidence: 63%
“…32 When exposed to a higher concentration of Qat the oral fibroblasts and keratinocytes underwent programmed cell death in a process involving reactive oxygen species. 33 Moreover, the study also found that oxidative stress can occur in oral cells exposed to Qat. If this occurs in vivo, it could lead to a host of cellular and tissue responses such as increased or decreased proliferation, increased keratotic differentiation and damage to macromolecules like DNA.…”
Section: Qat Use and Effects On Healthmentioning
confidence: 81%